2012
DOI: 10.1111/j.1365-2834.2012.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating demographic, work-related and job satisfaction variables as predictors of motivation in Greek nurses

Abstract: The constantly changing health sector requires that human resources and job context be a priority for health administrators. By promoting nurses' satisfaction and efficacy, an improvement in service quality is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 32 publications
4
88
2
6
Order By: Relevance
“…The structure of the Kenyan public hospitals is that decisions are made from the central government; these young nurses may feel they are not participating adequately in decision and policy making thus feeling dissatisfied with their job. All the nurses regardless of age were relatively dissatisfied with their benefits (see Table 8), contradicting the findings of Gaki [22] who suggested that remuneration especially concerned older nurses. The satisfaction with benefits in this study also did not significantly differ with job experience whereas Li et al [2] found that there is more satisfaction when one has a longer work experience.…”
Section: 6contrasting
confidence: 56%
See 2 more Smart Citations
“…The structure of the Kenyan public hospitals is that decisions are made from the central government; these young nurses may feel they are not participating adequately in decision and policy making thus feeling dissatisfied with their job. All the nurses regardless of age were relatively dissatisfied with their benefits (see Table 8), contradicting the findings of Gaki [22] who suggested that remuneration especially concerned older nurses. The satisfaction with benefits in this study also did not significantly differ with job experience whereas Li et al [2] found that there is more satisfaction when one has a longer work experience.…”
Section: 6contrasting
confidence: 56%
“…The nurses were most satisfied with work worth to self and others, supporting findings by Doef et al [17] who found that nurses in East Africa feel more accomplished. South African nurses were found to be moderately accomplished Gaki et al [22] The findings from South Africa can be compared with those in Kenya since there are cultural similarities between the two countries.…”
Section: Subscales Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Job satisfaction is related to organization's productivity and efficiency (Koustelios, 2001), employees' loyalty (Matzler, & Renzl, 2006) and creativity (Gaki et al, 2013) as well as school performance (Caprara et al, 2006;Saiti, 2007). Some theorists have specified the job satisfaction as a multifaceted construct which includes different components.…”
Section: Internal and External Factors Of Job Satisfactionmentioning
confidence: 99%
“…Regarding position, it is possible to assume that supervisors or directors have better incomes and more autonomy, in addition to more favorable physical work conditions and a greater feeling of professional satisfaction. It is not surprising that they hold higher WS levels, according to what has already being identified on an international study (22) . In contrast, undergraduate or graduated professionals without holding a position may feel upset with allegedly professional stagnations.…”
Section: We Have a Team Of Nursing Technicians With A Nursing Degree mentioning
confidence: 99%